MEMBANGUN INTEGRITAS PENEGAK HUKUM BAGI TERCIPTANYA PENEGAKAN HUKUM PIDANA YANG BERWIBAWA - Ridwan, Ridwan (Jurnal Media Hukum, 2012)
The way a legal system works determines how well law enforcement will be. A legal system consists of structure, substance and culture, of each must work in a system. In order that a legal system works properly, the law enforcers must be able to increase their knowledge on law and divinity so that they are able to comprehend law more broadly. In other words, law is not taken merely as a text in a constitution. As a system, the most important aspect is the culture of the law because it functions as the driving force that leads people to abide the law. In addition, in order to establish the integrity of legal enforcers, the implementation of integrated judicial system is also needed. Therefore, the role of supreme court as the highest supervisor of judges is also necessary.